2021
DOI: 10.1155/2021/4871453
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Iron Nanoparticles from Spinach Leaf and Banana Peel Aqueous Extracts and Evaluation of Antibacterial Potential

Abstract: Spinacia oleracea (spinach) and Musa acuminata (banana) were chosen for the study, and aqueous extracts of spinach leaf extract (SLE) and banana peel extract (BPE) were prepared for the synthesis of iron nanoparticles (FeNPs), and their antibacterial potential against pathogenic bacteria Bacillus subtilis (MTTC 1133) and Escherichia coli (MTTC 62) was evaluated. In 10 minutes at 60°C, the color of the mixture (FeCl3+SLE) changed from light green to dark blackish-brown, and the color of the mix (FeCl3+BPE) chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Experimental studies have confirmed that superparamagnetic iron oxide nanoparticles obtained using this co-precipitation method, in which CTS protects the surface, have excellent antibacterial activity against the Gram-negative bacteria Pseudomonas aeruginosa (P. aeruginosa) and E. coli [57]. Spinach leaf extract and banana peel have also been considered for the prepa-ration of iron nanoparticles [58]. The synthesised nanoparticles exhibited antimicrobial activity against two foodborne bacteria, i.e., Bacillus subtilis (B. subtilis) and E. coli, while remaining non-toxic against Drosophila melanogaster (D. melanogaster) in vivo.…”
Section: Introductionmentioning
confidence: 71%
“…Experimental studies have confirmed that superparamagnetic iron oxide nanoparticles obtained using this co-precipitation method, in which CTS protects the surface, have excellent antibacterial activity against the Gram-negative bacteria Pseudomonas aeruginosa (P. aeruginosa) and E. coli [57]. Spinach leaf extract and banana peel have also been considered for the prepa-ration of iron nanoparticles [58]. The synthesised nanoparticles exhibited antimicrobial activity against two foodborne bacteria, i.e., Bacillus subtilis (B. subtilis) and E. coli, while remaining non-toxic against Drosophila melanogaster (D. melanogaster) in vivo.…”
Section: Introductionmentioning
confidence: 71%
“…As a result, the antibacterial activity is consistent and effective with green-synthesized iron and silver nanoparticles in different plant extracts reported in earlier studies [ 10 , 38 , 39 ]. The antibacterial potential of biogenic iron nanoparticles synthesized from spinach leaves extract against B. subtilis (23.56 ± 1.00) and E. coli (20.33 ± 0.58) were reported [ 40 ]. Silver nanoparticles showed prominent antibacterial activity, with a zone of inhibition found in the case of E. coli (17.00 ± 0.14 mm), Shigella sp.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been shown that these NPs penetrate microbial membranes and result in electrolyte leakage, which eventually results in cell death. Nanomaterials can increase the permeability of bacterial cell membranes, prevent bacterial protein denaturation and DNA replication and release silver ions (see Figure 6 for various mechanisms) ( Tyagi et al, 2021 ).…”
Section: Biomedical Applicationsmentioning
confidence: 99%